2016
DOI: 10.3390/nu8100599
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of SGC-7901 Tumor Xenografts Was Suppressed by Chinese Bayberry Anthocyanin Extract through Upregulating KLF6 Gene Expression

Abstract: To investigate the antitumor effect of anthocyanins extracted from Chinese bayberry fruit (Myrica rubra Sieb. et Zucc.), a nude mouse tumor xenograft model was established. Treatments with C3G (cyanidin-3-glucoside, an anthocyanin) significantly suppressed the growth of SGC-7901 tumor xenografts in a dose-dependent manner. Immunohistochemical staining showed a significant increase in p21 expression, indicating that the cell cycle of tumor xenografts was inhibited. qPCR screening showed that C3G treatment up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Two human gastric cancer cell lines, i.e., SGC-7901 and BGC-823, were used in the cell viability assay. These classic cell lines are commonly used to explore the effect of proliferation inhibition of gastric cancer cells [11,23,49]. The two cell lines were cultured in RPMI-1640 medium (10% FBS and 1 × HEPES) and maintained at 37 • C in a humidified incubator containing 5% CO 2 .…”
Section: Cell Culture and Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Two human gastric cancer cell lines, i.e., SGC-7901 and BGC-823, were used in the cell viability assay. These classic cell lines are commonly used to explore the effect of proliferation inhibition of gastric cancer cells [11,23,49]. The two cell lines were cultured in RPMI-1640 medium (10% FBS and 1 × HEPES) and maintained at 37 • C in a humidified incubator containing 5% CO 2 .…”
Section: Cell Culture and Cell Viability Assaymentioning
confidence: 99%
“…Flavonoids are also thought to be important dietary ingredients and have also been intensively studied for their health benefits to humans and animals [7,8]. Flavonoids produced by plants have diverse biological activities, including anti-inflammatory [9], antioxidant [10], and anti-cancer activities [11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the tumor-suppressing effect of anthocyanins can also be seen in other pathways, such as interfering with cell cycle or inducing apoptosis. Wang et al (18) showed the proliferation of gastric cancer cells can be inhibited by a kind of anthocyanins, through upregulating the expression of the KLF6 gene, a novel tumor suppressor gene (51), which can increase the expression of p21 and decrease the expression of CDK4 and Cyclin D1 in a p53-independent manner. Moreover, there were also studies that showed the cellular apoptosis can be induced by anthocyanins through p38/p53 and p38/cjun signaling pathways intrinsically and extrinsically or through caspase-3 related mitochondrial-mediated pathways (52).…”
Section: Mechanismsmentioning
confidence: 99%
“…Some in vivo studies in animals showed the inhibitory effect of anthocyanins on the skin cancer (15). Furthermore, there were also in vitro studies that illustrated anthocyanins could inhibit gastric cancer via antioxidant or anti-inflammation (16), induction of apoptosis (17), and blockage of cell cycle (18).…”
mentioning
confidence: 99%
“…Anthocyanin plays critical roles in protecting plants from abiotic and biotic stresses (Kong et al , ) and also is the important component of quality traits in horticultural products (Diretto et al , ). Anthocyanins are also suggested to provide a number of benefits for human health, such as aiding prevention of cancer and cardiovascular diseases (Middleton et al , ; Zafra‐Stone et al , ; Wang et al , ).…”
Section: Introductionmentioning
confidence: 99%